Cosmopolitan Makassar: Continuing the Ambiguity of Indonesia’s Modern Cities - Ilham Ilham; Ida Liana Tanjung; Cho Tae Young (JURNAL GEOGRAFI, 2026)
This article examines the formation of modernity in Makassar City during the first two decades of the 21st century within the framework of contemporary urban spatial transformation. This period is marked by modern projects such as the revitalization of Losari Beach, coastal reclamation, the development of the Center Point of Indonesia area, the smart city program, and the hosting of international festivals. These efforts constitute a form of promoting Makassar as a “world city” that is cosmopolitan and globally competitive. This research aims to explain how these modernity projects are manifested, negotiated, and reproduced within a historical context. It analyzes the ongoing efforts of the city government, the business sector, and various communities in shaping a cosmopolitan Makassar in the 21st century. The study uses historical methods, including heuristics (collecting archives, policy documents, media reports, and interviews), source criticism, contextual interpretation, and historiographical reconstruction. The analysis is conducted diachronically to trace the continuity of previous developmental legacies, and synchronically to examine the power relations among various stakeholders. The results show the existence of contradictions as as a tangible form of urban modernity. Makassar's modernization reproduces the old spatial pattern—that is, the separation between the modern center and the underdeveloped periphery—while presenting a performative cosmopolitanism focused on image and symbolism. Modernity follows global aesthetic trends and market demands; however, this condition results in evident social and ecological inequalities. This research contributes to the historiography of Indonesian urban history by positioning Makassar City as an important case outside of the Java-centric narrative and offering the concept of “ambiguous modernity” as an inherent characteristic of postcolonial cities, not merely as a policy anomaly.